Fa’aliyyatu Namudzaj Flipped Classroom ‘Ala Tahsini Maharati Al-Qiraah Fi Al-Madrasah Al-Tsanawiyah Al-Hukumiyah - Syarifah Jinan; Muhammad Zaenuri; Sukirman Sukirman; Muhammad Nur Kholis (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
n the process of teaching the Arabic language, including reading skills, there are still many students who struggle with learning it. Teachers also do not use methods that could facilitate students' understanding of the material presented. This study aims to analyze the effectiveness of the Flipped Classroom learning model in improving reading skills (maharah Qira'ah) in class X students at Madrasah Aliyah Negeri Sukoharjo. This research is a quantitative research using pre-experimental method with one-group pretest-posttest design, involving 30 students as samples. The research instruments were pretest and posttest tests to evaluate students' reading skills before and after the intervention. It was prepared based on the curriculum of Madrasah Aliyah Negeri Sukoharjo. The results showed a significant increase in posttest scores (82.00) compared to the pretest (54.33), with a statistical significance value of only 0.001. This increase shows the effectiveness of the Flipped Classroom model in improving students' reading skills. This model is considered effective because it has achieved the expected learning objectives, namely an increase in learning outcomes as evidenced by the results of posttest scores.